2012
DOI: 10.1021/jp212430a
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Signatures of Natural Sea Films from Middle Adriatic Stations

Abstract: Monolayer studies and a force-area quantification approach, in combination with electrochemical methods, are applied for physicochemical characterization of surface active substances (SAS) of the sea surface microlayers (MLs) from Middle Adriatic stations. Higher primary production during late spring-early autumn was reflected in the presence of MLs of higher surfactant activity containing on average molecules of lower molecular masses (M(w) = 0.65 ± 0.27 kDa) and higher miscibility (y = 6.46 ± 1.33) and elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…It could be learned from monolayer studies and a force-area quantification approach applied for physicochemical characterization of surface-active substances of the sea surface microlayer from Middle Adriatic stations (Frka et al 2012 ). Higher primary production during late spring-early autumn was reflected in the appearance of films of higher surface activity containing compounds of lower molecular masses ( M w = 0.65 ± 0.27 kDa) and higher miscibility ( y = 6.46 ± 1.33), and elasticity modulus ( E isoth = 18.35 ± 2.02 mN m −1 ) in comparison to structural parameters ( M w = 2.15 ± 1.58 kDa; y = 3.51 ± 1.41; E isoth = 6.41 ± 1.97 mN m −1 ) obtained for samples collected in a period of lower biological production (Frka et al 2012 ). Force-area studies performed on chlorophyll-a surfactants at the air-water interface revealed the following values of y = 5.3–8.2, A lim = 59–67 Ǻ 2 molec −1 , E isoth = 69–95 mN m −1 and exhibited 2D solid-like behavior (Periasamy 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could be learned from monolayer studies and a force-area quantification approach applied for physicochemical characterization of surface-active substances of the sea surface microlayer from Middle Adriatic stations (Frka et al 2012 ). Higher primary production during late spring-early autumn was reflected in the appearance of films of higher surface activity containing compounds of lower molecular masses ( M w = 0.65 ± 0.27 kDa) and higher miscibility ( y = 6.46 ± 1.33), and elasticity modulus ( E isoth = 18.35 ± 2.02 mN m −1 ) in comparison to structural parameters ( M w = 2.15 ± 1.58 kDa; y = 3.51 ± 1.41; E isoth = 6.41 ± 1.97 mN m −1 ) obtained for samples collected in a period of lower biological production (Frka et al 2012 ). Force-area studies performed on chlorophyll-a surfactants at the air-water interface revealed the following values of y = 5.3–8.2, A lim = 59–67 Ǻ 2 molec −1 , E isoth = 69–95 mN m −1 and exhibited 2D solid-like behavior (Periasamy 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The issue is further compounded by a high degree of spatial and temporal variability in total surfactant amount and in the chemical composition of the surfactant pool, both in the short-term and seasonally (Gašparović et al, 2011;Schmidt and Schneider, 2011;Wurl et al, 2011;Laß et al, 2013;Schneider-Zapp et al, 2014;Pereira et al, 2016). Compounds that contribute little to organic matter by mass, such as lipids, may have a strong influence on the physicochemical, and structural properties of the SML (Frka et al, 2012). Compositional variations in SML biosurfactants deriving from organic matter dynamics in natural waters and their specific impact on k w still needs to be assessed (Pogorzelski et al, 2006).…”
Section: Do We Need To Better Resolve the Air-sea Interface To Enablementioning
confidence: 99%
“…The ocean covers around 71 % of the Earth's surface and acts as a source and sink for atmospheric gases and particles. However, the complex interactions between the marine boundary layer (MBL) and the ocean surface are still largely unexplored (Cochran et al, 2017;de Leeuw et al, 2011;Gantt and Meskhidze, 2013;Law et al, 2013). In particular, the role of marine organic matter (OM) with its sources and contribution to marine aerosol particles is still elusive.…”
Section: Introductionmentioning
confidence: 99%